2006
DOI: 10.2225/vol9-issue5-fulltext-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two total RNA extraction protocols using the marine gorgonian coral Pseudopterogorgia elisabethae and its symbiont Symbiodinium sp

Abstract: Marine invertebrates such as soft corals are important sources of secondary metabolites with promising biomedical applications and commercial value. RNA isolation in conjunction with reverse-transcriptase polymerase chain reaction (RT-PCR) are valuable tools utilized to study the molecular elements involved in secondary metabolite production and functional genomics. Two total RNA extraction protocols were compared using fresh tissue and flash frozen preparations from the coral Pseudopterogorgia elisabethae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
1
17
0
1
Order By: Relevance
“…The procedures for these 3 methods are summarized in the schematics in Figure 2. Some studies have suggested the yield of RNA obtained using the GITC-based method can be higher than the column based method for some samples [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The procedures for these 3 methods are summarized in the schematics in Figure 2. Some studies have suggested the yield of RNA obtained using the GITC-based method can be higher than the column based method for some samples [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…from human, animal or plant), the sampling procedures (biopsy material, single cell sampling, laser micro-dissection, tissue) as well as the method of RNA isolation (total RNA or polyadenylated RNA methods) differ very often from one laboratory to another (Bustin et al, 2005;Pfaffl, 2004). As a matter of example the use of liquid extraction by Trizol gives different results (low quality) when compared to column based extraction method (Santiago-Vazquez, Ranzer, and Kerr, 2006). Furthermore, the use of kits containing phenol (such as Trizol ® or Qiazol ®) is risky.…”
Section: Introductionmentioning
confidence: 99%
“…Minogue et al [61] Rat NP, AF and AC tissues Modified TRIspin method Lee et al [128] In this study, we chose to use TRIzol for the RNA extraction as some studies have suggested the yield of RNA obtained using the guanidine isothiocyanate (GITC) based method can be higher than the column based method for some samples [129][130][131][132]. The studies in Table 3-2 either used TRIzol extraction or TRIspin method for RNA isolation.…”
Section: Tissue Extraction Referencementioning
confidence: 99%
“…RNeasy) are two commonly used methods for RNA extraction. Some studies have suggested the yield of RNA obtained using the GITC-based method can be higher than the column based method for some samples [129][130][131][132]. Thus we used GITC based TRIzol to lyse the cells.…”
Section: Comparison Of Rna From Propanol Precipitation and Column Basmentioning
confidence: 99%
See 1 more Smart Citation